Cumulative Corticosteroid Doses and Osteoporosis in Patients with Multiple Sclerosis - Şule Arslan,; Reyhan Çeliker,; Rana Karabudak, (Archives of Rheumatology, 2010)
Objective: Multiple sclerosis (MS) is an inflammatory demyelinating disorder and corticosteroids used for the treatment of attacks are known to cause osteoporosis. Although osteoporosis is a known potential complication, many patients do not receive treatment to prevent bone loss. The aim of this study was to assess the relationship between cumulative doses of corticosteroids and bone mineral density (BMD) in MS patients. Materials and Methods: Twenty-two patients with MS (15 women, 7 men) and 22 age- and sex-matched subjects were enrolled into the study. Lumbar and femoral BMDs were measured using dual energy X-ray absorptiometry (DXA). Mobility and ambulation scales were also evaluated. Corticosteroid use was determined from an interviewer-administered questionnaire and patient records. Result: Lumbar and femoral BMDs were significantly lower in MS patients compared to the control group (p<0.05). 18.2% of the MS patients had no restriction in activities of normal employment and domestic life when assessed with Kraft Mobility Scale. Only 22.7% of the MS patients were fully ambulant when evaluated with Scranton Ambulation Scale. Cumulative dose was negatively correlated with lumbar BMD measurements (r=-0.505, p=0.017). Conclusion: Corticosteroids are an important part of the MS therapy and their use results in osteoporosis. Thus, cumulative corticosteroid dose should be determined and BMD measurements of the patients should be taken before treatment to determine those at high risk of osteoporosis, and preventive measures should be undertaken. (Turk J Rheumatol 2010; 25: 191-5)